ANALISIS SISTEMATIS TERHADAP MODEL ADMINISTRASI PEMBANGUNAN DI INDIA DAN INDONESIA - Pramesti Dwipayana; Aminullah (As-Sulthan Journal of Education, 2026)
Development administration plays a crucial role in determining the success of national development, particularly in addressing the challenges of inequality, the effectiveness of public services, and governance. India and Indonesia, as developing countries with large populations, have distinct government systems and therefore implement different development administration models. This study aims to systematically analyze and compare the development administration models implemented in India and Indonesia. This study uses a qualitative approach with a comparative descriptive method. Data were obtained through a literature review sourced from scientific journals, policy documents, and official government publications. The analysis was conducted by describing each country's development administration model and then comparing their institutional structures, division of authority, and development implementation mechanisms. The results show that India tends to implement a centrally coordinated development administration model within a federal framework, with flexibility in implementation at the state level. Meanwhile, Indonesia has developed a decentralized development administration model with broad authority for local governments. These differences affect the effectiveness of coordination, institutional capacity, and the equitable distribution of development outcomes. This study concludes that no single development administration model is entirely ideal, as its success is strongly influenced by the institutional context and government capacity. These findings are expected to provide conceptual contributions to the development of development administration studies and serve as a basis for consideration in formulating development policies in developing countries.